STUDI PERBANDINGAN KEPATUHAN WAJIB PAJAK DALAM PELAPORAN SURAT PEMBERITAHUAN TAHUNAN SEBELUM DAN SESUDAH PENERAPAN METODE E-FILLING (Studi Pada KPP Pratama Sumbawa Besar) - S Syafruddin; Binar Dwiyanto Pamungkas; H Hamdi (Jurnal Ekonomi & Bisnis, 2020)
This study aims to compare the obedience level of taxpayers in reporting annual notification letters (SPT) before and after the application of the e-filling method at KPP Pratama Sumbawa Besar. Type of this study was comparative study. The types of data used in this study were primary data obtained through questionnaires and secondary data that have taken from documents at KPP Pratama Sumbawa Besar. The populations in this study were 13.047 taxpayers. Technique used to determine sample was accidental sampling. The data analysis technique used was the paired sample-test analysis and the normality test. The results of this study showed that there were differences in the level of taxpayer compliance before and after the application of the e-filling method in the annual notification letter (SPT) in KKP Pratama Sumbawa Besar. The application of the e-filling method had a positive and significant effect toward taxpayer compliance at KPP Pratama Sumbawa. This means that the higher the level of application of the e-filling method in the annual SPT reporting, the level of taxpayer compliance at KKP Pratama Sumbawa Besar will increase.